The Influence of Social Support during the Primary Years of Schooling among Tertiary Students towards Their Social Competence - Bacus, Hans Glazien S.; Borbonga, Francis Angelo L.; Casas, Janna Marie C.; Catubigan, Shekinah Gliel F.; Quinapondan, Yezabelle F.; Gagani, Flordeliza S.; Chan, Clyde I.; Gagani, Ray Ferdinand M. (Newinera Publisher, 2024)
This study investigates the influence of social support during primary years on the development of social competence in tertiary education. Recognizing the pivotal role of early experiences in shaping lifelong outcomes, the researchers draw upon extensive research to investigate the nuanced relationships that unfold across these critical stages of human development. Hence, this study aims to probe the relationship between social support during the primary years and self-competence among the randomly selected tertiary students of a private sectarian University in Cebu City, Philippines through a descriptive correlational study. Data were gathered online and face to face using valid and reliable 4-point adapted Likert-type survey questionnaires. Results revealed that both social support (x̄ = 3.14, SD = 0.87) and social competence (x̄ = 2.84, SD = 0.76) were described as high. Pearson's r correlation was also found to be significant, r(180) = 0.17, p = .02177, p<0.5, thus rejecting the null hypothesis and concluding that there is a relatively weak positive correlation (r = 0.17) between the levels of self-confidence and self-efficacy among the students while engaging in online learning. In essence, the findings imply that students perceiving elevated levels of social support during their formative years are likely to exhibit heightened social competence later in life. This study recommends that future research endeavors adopt an extended timeframe; tracking participants from primary through tertiary education as such, an approach would provide insights into how these factors evolve and exert lasting effects.